Kajian Evaluasi Kinerja Pelayanan Transportasi Antar Moda Di Pulau Batam - Noviyanti, Noviyanti (Warta Penelitian Perhubungan, 2010)
Integration antannoda at international airports and seaports in Indonesia's need to be supported withfacilities/ tenninals far integration antannoda integrated in order to improve the quality of transportationservice on service users. The important role of integrated facilities far transfer nwde still needsto be organized with a facilib.J poliaj / antannoda integrated tenninal. Port and airport facilities inaccordance with the wishes of the user port and airport services that meet the criteria as ports andairports with integrated services in order to support the development of antannoda transport, therebyincreasing the transportation service effectively and efficiently.Data were analyzed using descriptive statistics, further analysis of transportation service performanceusing analyti.cal tools antannoda Importance Performance Analysis (IPA) and the CustomerSatisfaction Index (CSI). Based on the analysis, it is knawn that ports and airports are being evaluatedmeet the criteria for supporting the transport antannoda but there antannoda transportationservice facilities slwuld be improved anwng other facilities in ports/ airports, convenience of alternativeroutes to the bus station, port or airport , availabi1ity of tickets reservation service counter facilities,the dismissal of public transport passenger bus stop near the port/ airport, ease to get traveltickets with a choice of various kinds of advanced modes.Keywords: Inter-Mode, Transport Sennce, Performance.